2021
DOI: 10.1080/21623945.2021.1979277
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose cotransporter 2 inhibitor dapagliflozin depressed adiposity and ameliorated hepatic steatosis in high-fat diet induced obese mice

Abstract: With the increasing obesity prevalence, the rates of obesity-related diseases, including type 2 diabetes, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases, have increased dramatically. Dapagliflozin, one of the sodium glucose cotransporter inhibitors, not only exerts hypoglycaemic effects through increasing urinary glucose excretion but alsoreprograms the metabolic system, leading to benefits in metabolic and cardiovascular diseases. In this study, pre-established obese mice on a high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Administration of SGLT-2i leads to net loss of calories and consequent attenuation of body weight gain, while reducing the accumulated white adipose tissue [ 99 , 105 , 106 , 107 ]. In fact, it has been found that SGLT-2i promote weight loss through improvement of systemic IR, increased body temperature and basal metabolism via regulation of the AMP/ATP ratio [ 19 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
See 3 more Smart Citations
“…Administration of SGLT-2i leads to net loss of calories and consequent attenuation of body weight gain, while reducing the accumulated white adipose tissue [ 99 , 105 , 106 , 107 ]. In fact, it has been found that SGLT-2i promote weight loss through improvement of systemic IR, increased body temperature and basal metabolism via regulation of the AMP/ATP ratio [ 19 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
“…However, it should be noted that not all studies point towards a beneficial effect of SGLT-2i on body weight. Several studies have shown that administration of SGLT-2i does not exert any significant effect on body weight gain, epididymal fat weight or food intake [ 30 , 105 , 110 , 111 ]. In addition, although several studies reported strong effects of low dose ipragliflozin ( Table 4 ) on weight loss [ 100 , 112 , 113 ], supplementation of an AMLN diet with 40 mg ipragliflozin/kg for 8 weeks did not significantly alter the body weight of AMLN diet fed mice, while it improved liver function, hepatic fibrosis and NA score [ 114 ].…”
Section: Sglt-2 Inhibitors In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, following DAPA treatment, obese mice fed a high-fat diet experienced weight loss, primarily through reduction in subcutaneous and visceral fat pools. Additionally, DAPA treatment promotes mitochondrial biogenesis and increases cellular energy expenditure [ 15 , 16 ]. Notably, the expression of UCP1 in both WAT and BAT was significantly elevated, indicating DAPA’s ability to promote the activation of BAT and the “browning” of WAT [ 14 ].…”
Section: Introductionmentioning
confidence: 99%